2012
DOI: 10.1111/j.1365-2869.2012.01010.x
|View full text |Cite
|
Sign up to set email alerts
|

Internight sleep variability: its clinical significance and responsiveness to treatment in primary and comorbid insomnia

Abstract: SUMMARYAlthough sleep diary and actigraphy data are usually collected daily for 1 or 2 weeks, traditional analytical approaches aggregate these data into mean values. Internight variability of sleep often accompanies insomnia. However, few studies have explored the relevance of this ÔconstructÕ in the context of diagnosis, clinical impact, treatment effects and ⁄ or whether having Ôvariable sleepÕ carries any prognostic significance. We explored these questions by conducting secondary analyses of data from a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 26 publications
5
37
0
Order By: Relevance
“…Although several CBT-I trials have demonstrated improvement in both sleep diary and actigraphic variables, a number of studies have demonstrated changes in only sleep diary data. 31,32 Especially relevant to the current study, in Bootzin and Steven's trial of CBT-I in adolescents with comorbid insomnia and substance use, a similar phenomenon was observed in that sleep diary results indicated significant changes after treatment whereas actigraphy-measured sleep did not change. 13 The lack of change in actigraphic sleep data compared to the moderate to large changes in sleep-diary and self-report data in our trial could be reflective of several issues related to using actigraphy in context of a brief intervention.…”
Section: Discussionmentioning
confidence: 65%
“…Although several CBT-I trials have demonstrated improvement in both sleep diary and actigraphic variables, a number of studies have demonstrated changes in only sleep diary data. 31,32 Especially relevant to the current study, in Bootzin and Steven's trial of CBT-I in adolescents with comorbid insomnia and substance use, a similar phenomenon was observed in that sleep diary results indicated significant changes after treatment whereas actigraphy-measured sleep did not change. 13 The lack of change in actigraphic sleep data compared to the moderate to large changes in sleep-diary and self-report data in our trial could be reflective of several issues related to using actigraphy in context of a brief intervention.…”
Section: Discussionmentioning
confidence: 65%
“…Therefore, multiple methods are essential to capture both subjective and objective measures of sleep, preferably with serial assessment. In addition to assessing central tendency, within-subject variability and night-to-night variability of sleep patterns must also be considered, as these are increasingly recognized as important determinants of disease severity and treatment outcome [131][132][133][134].…”
Section: Measurement Issuesmentioning
confidence: 99%
“…These findings are consistent with prior studies in young and middle-aged adults. 13,14 Extending from previous research, this study showed that a 4-session BBT-I was efficacious in reducing sleep variability in older adults with chronic insomnia. The decreases in percentage in SOLs variability and TSTa variability were comparable to those in a prior study implementing a 4-session CBT-I in middle-aged adults.…”
Section: Reduction Of Sleep Variability In Bbt-imentioning
confidence: 51%
“…Sanchez-Ortuno and Edinger found that higher baseline sleep variability was associated with worse sleep outcomes following CBT-I, 13 …”
Section: Night-to-night Sleep Variability In Older Adults With Chronimentioning
confidence: 99%
See 1 more Smart Citation